2018
DOI: 10.1038/s41386-018-0232-4
|View full text |Cite
|
Sign up to set email alerts
|

Can neuroimaging help combat the opioid epidemic? A systematic review of clinical and pharmacological challenge fMRI studies with recommendations for future research

Abstract: The current opioid epidemic is an urgent public health problem, with enormous individual, societal, and healthcare costs. Despite effective, evidence-based treatments, there is significant individual variability in treatment responses and relapse rates are high. In addition, the neurobiology of opioid-use disorder (OUD) and its treatment is not well understood. This review synthesizes published fMRI literature relevant to OUD, with an emphasis on findings related to opioid medications and treatment, and propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 136 publications
(210 reference statements)
5
36
0
Order By: Relevance
“…We found that conditioned heroin withdrawal motivated heroin intake and engaged brain regions that are associated with negative emotional learning, particularly extrahypothalamic and hypothalamic stress/arousal circuitries. These circuits are consistent with and extend fMRI findings in individuals with OUD on drug cue reactivity tasks (22,23). Thus, we argue that conditioned cues can maintain compulsive drug use by removing aversive states We anatomically segregated the cluster defined by the statistically significant heroin-access (ShA versus LgA) × cue (saline paired versus naloxone paired) interaction (shown in Figure 1C) into 19 ROIs using a standard rat atlas (14).…”
Section: Further Information Can Be Found In Supplemental Methods Andsupporting
confidence: 79%
See 2 more Smart Citations
“…We found that conditioned heroin withdrawal motivated heroin intake and engaged brain regions that are associated with negative emotional learning, particularly extrahypothalamic and hypothalamic stress/arousal circuitries. These circuits are consistent with and extend fMRI findings in individuals with OUD on drug cue reactivity tasks (22,23). Thus, we argue that conditioned cues can maintain compulsive drug use by removing aversive states We anatomically segregated the cluster defined by the statistically significant heroin-access (ShA versus LgA) × cue (saline paired versus naloxone paired) interaction (shown in Figure 1C) into 19 ROIs using a standard rat atlas (14).…”
Section: Further Information Can Be Found In Supplemental Methods Andsupporting
confidence: 79%
“…Several other regions exhibited activation patterns that were similar to those seen in the hypothalamic cluster and amygdala ( Table 1). Many of these regions have been implicated in emotional learning and are hypothesized to be dysregulated in addiction (2,22,23). These include the lateral hypothalamus, dorsomedial nucleus of the thalamus, ventrolateral thalamus, and dorsal striatum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory control impairment makes it difficult for individuals to resist the temptation of drug cues and impulsive thoughts and behaviors of intake. Moreover, neuroimaging studies have further demonstrated that, relative to healthy groups, heroin addict groups exhibit abnormal structures and lower levels of activation in brain regions related to inhibitory control during the Go/No-Go task, including impairments in the bilateral medial prefrontal gyrus, bilateral anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (DPFC), left middle frontal gyrus (MFG), and left insular and bilateral inferior frontal gyrus (IFG) (Fu et al, 2008;Luijten et al, 2014;Moningka et al, 2018). Inhibitory control failure and associated brain dysfunction are key underlying factors of relapse and addiction (Su et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Human imaging studies investigating the opioid effects on the brain have been reviewed recently (23) and discussed (24) in the context of the 3-stage addiction cycle framework (5), showing in particular that negative affect during opioid withdrawal is associated with enhanced beta power activity and increased connectivity strength between the amygdala and ventral striatum-two main reward and aversion centers. In addition, human neuroimaging was performed under conditions of protracted opioid abstinence, and these studies have been reviewed previously (25).…”
mentioning
confidence: 99%